Summary and Enlightenment of Foreign Research on Digital Inclusion - Guo Chunxia; Yao Xin (Zhishi guanli luntan, 2023)
[Purpose/Significance] Grasp the characteristics of foreign digital inclusion research, promote domestic theoretical research and practice, and accelerate the process of digital China and Chinese path to modernization. [Method/Process] Through the investigation and content analysis of the core collection of Web of Science, this paper combed the research contents and methods of digital inclusion abroad, summarized the research characteristics and drew inspiration. [Result/Conclusion] The total number of research results on digital inclusion is relatively small, and the research methods are diverse. Its research covers and transcends the digital divide research, and mainly focuses on various types of digital vulnerable groups and digital inclusion projects to carry out research on digital inclusion triggers, measurement indicators, framework models, strategies to achieve digital inclusion, and library digital inclusion services. Inspirations for domestic digital inclusion research include: strengthening the community research of digital vulnerable groups, carrying out macro-research based on field research, paying attention to the popularization of digital education, paying attention to interdisciplinary cooperation research, innovating research theories and methods, paying attention to strengthening cross-border collaborative project research, and promoting the theory and practice of digital inclusion are the social responsibilities of the library community in the digital era.